Antibacterial Activities of Micromonospora sp. 2310 Isolated from Marine Sediment, Baru Island, West Kalimantan - Risa Nofiani; Puji Ardiningsih (Jurnal Kimia Sains dan Aplikasi, 2022)
The increase in cases of antibiotic resistance and the discoveries cessation of new classes of antibiotics encourages the exploration of various microorganism sources from unique environments to produce antimicrobial compounds. This study aimed to characterize actinobacteria isolated from marine sediment and evaluate the best medium and incubation time for its antibacterial activities. The sediment sample collected from Buru Island, West Kalimantan, was isolated actinobacteria and characterized based on morphological, biochemical, and molecular (16S rRNA gene) approaches. Antibacterial activities were tested using the well-diffusion methods. Twelve suspected colonies were successfully purified. Isolate 2310, which showed a different morphology colony, was close to Micromonospora based on morphological, biochemical, and 16S rRNA gene analysis and called Micromonospora sp. 2310. Extract isolate 2310 prepared from AM medium showed the best medium for antibacterial activities compared with the other media due to activity against 5 of 6 bacteria, namely Staphylococcus aureus ATCC 12600, Bacillus subtilis ATCC 6051, Salmonella enterica ATCC 14028, Escherichia coli ATCC 11775, Pseudomonas aeruginosa ATCC 9721 except Mycobacterium smegmatis ATCC 14468. Therefore, Micromonospora sp. 2310 could be considered a great potential antibacterial producer.